Studi Islam Dalam Dinamika Peradaban Modern: Relevansi Dan Tantangannya Di Era Globalisasi Dan Digitalisasi - Titin Suhartini; Leni Latifah; Mawar Holipatul Mar'ah; Esa Masrohatul Bahiyah; Husnul Jauharu Mu'awanah (Multidisciplinary: Journal of Education an Learning, 2026)
Islamic Studies is an academic discipline that plays an important role in understanding Islam comprehensively while responding to social change. In the context of modern civilization, globalization and digitalization have transformed the production, dissemination, and practice of religious knowledge among Muslim communities. These changes create opportunities for the development of Islamic Studies, but also generate epistemological and socio-religious challenges, such as fragmented religious authority, religious misinformation, and digital-based extremism. This article aims to analyze the relevance of Islamic Studies within the dynamics of modern civilization and to examine the challenges it faces in the era of globalization and digitalization. This study employs a qualitative approach using library research methods based on relevant scholarly books and journal articles. Data are analyzed through descriptive-analytical techniques. The findings indicate that Islamic Studies remains relevant in promoting a moderate and contextual understanding of Islam, highlighting the importance of strengthening methodological frameworks and digital religious literacy in modern society.